Trastuzumab emtansine vs lapatinib and capecitabine in HER2-positive metastatic breast cancer brain metastases: A real-world study - Thibaut Sanglier; Jinjoo Shim; Neil Lamarre; Claudia Peña-Murillo; Vincent Antao; Filippo Montemurro (Breast, 2023)
Background: Trastuzumab emtansine (T-DM1) has demonstrated improvements in survival and neurological symptoms in patients with breast cancer with brain metastases (BCBM). This real-world study investigated the effectiveness of T-DM1 versus lapatinib plus capecitabine (LC) in patients with BCBM. Methods: This retrospective, observational study evaluated patients with HER2–positive BCBM using a real-world database. Eligible patients had initiated T-DM1 or LC with a prior diagnosis of brain metastasis and ≥1 prior metastatic breast cancer treatment. The primary endpoint was overall survival (OS); secondary endpoints were time to next relevant treatment or death (TTNT) and real-world progression-free survival (rwPFS). An inverse probability of treatment weighting (IPTW) approach was used to account for differences in potential baseline characteristics between treatment groups. Outcomes were described using the Kaplan-Meier method, and the average treatment effect of initiating T-DM1 versus LC was estimated using weighted Cox proportional hazard models and hazard ratio (HR). Results: A total of 214 patients were available for analysis (T-DM1, n = 161; LC, n = 53). Demographics and baseline characteristics were generally well-balanced between treatment groups after weighting. After weighting, median OS was 17.7 (T-DM1) versus 9.6 (LC) months (HR, 0.55 [95% CI, 0.34–0.89]; P=0.013). Median TTNT was 9.0 (T-DM1) versus 6.0 (LC) months (HR, 0.55 [95% CI, 0.36–0.85]; P = 0.005). After weighting, median rwPFS was 6.0 (T-DM1) versus 4.0 (LC) months (HR, 0.50 [95% CI, 0.36–0.69]; P < 0.001). Conclusions: These results support the superior effectiveness and clinical relevance of T-DM1 versus LC in patients with HER2-positive BCBM in the real world.